Pharmaceutical Factors for Functional Independence Measure (FIM) in a Convalescent Rehabilitation Ward: using decision tree analysis and multivariate regression analysis - Itaya, Kazuhiro; Hirano, Iyori; Nakano, Hitoshi; Akagawa, Keiko; Kishimoto, Keiko; Osumi, Hiroyuki; Kumaki, Ryota; Otsubo, Hiroko (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2021)
We investigated the pharmaceutical factors affecting the functional independence measure (FIM) of adult patients in our convalescent rehabilitation ward.The subjects were 294 patients who were discharged from April 2018 to December 2019. The outcomes were motor FIM gain and motor FIM efficiency. From univariate analysis and decision tree analysis, age, renal function, cognitive function, sex, hypertension, number of drugs prescribed at discharge, hypnotics and anticholinergic drugs were related factors.Since it was found from the decision tree analysis that cognitive impairment had the greatest effect on motor FIM gain and motor FIM efficiency, multiple regression analysis was performed according to the presence or absence of cognitive dysfunction. In 82 patients with cognitive impairment, motor FIM gain was affected by the number of drugs prescribed at discharge (P = 0.001, β = -0.376), renal function (P = 0.010, β = -0.307). The use of hypnotics (P = 0.004, β = 0.327) and the number of drugs prescribed at discharge (P = 0.045, β = -0.236) affected the motor FIM efficiency, whereas in 212 patients without cognitive impairment, renal function affected both motor FIM gain and motor FIM efficiency (P = 0.046, β = -0.149)(P < 0.001, β = -0.286).Renal function was evaluated by standardized eGFR, but other parameters should be examined. In patients with cognitive impairment, both motor FIM gain and efficiency decreased as the number of drugs prescribed at discharge increased, and it was expected that the use of hypnotics suitable for individual patients increases motor FIM efficiency.